1998
DOI: 10.1080/02652039809374709
|View full text |Cite
|
Sign up to set email alerts
|

Determination of mineral contents in different kinds of milk and estimation of dietary intake in infants

Abstract: Concentrations of 11 minerals were determined in six kinds of milk (cow's milk-based formulae, breast-milk, soya milk, bottled milk, dried milk and evaporated milk). The contents of copper, magnesium, molybdenum, aluminium, barium and nickel were higher in soya milk than in any other kinds of milk. Except for nickel in soya milk, the dietary intakes of minerals were below or close to the intake recommended by the FAO/WHO.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
13
0
6

Year Published

2005
2005
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(20 citation statements)
references
References 20 publications
1
13
0
6
Order By: Relevance
“…The range of lead determined agrees reasonably well with most literature values (Ikem et al 2002, Moreno-Rojas 2002, Tripathi et al 1999, Rodríguez et al 1999, Biego et al 1998, Krachler et al 1998, Ursinyova and Hladikova 1997, Esteve et al 1994, Dabeka 1989, Dabeka and Mckenzie 1987,1988.…”
Section: Resultssupporting
confidence: 77%
“…The range of lead determined agrees reasonably well with most literature values (Ikem et al 2002, Moreno-Rojas 2002, Tripathi et al 1999, Rodríguez et al 1999, Biego et al 1998, Krachler et al 1998, Ursinyova and Hladikova 1997, Esteve et al 1994, Dabeka 1989, Dabeka and Mckenzie 1987,1988.…”
Section: Resultssupporting
confidence: 77%
“…The same proteins have been identified in mushroom, beans, soya beans, cabbage, wheat, and several other plants (Tjell et al 1983). Studies have shown that cadmium transfer via milk was low in rats and mice (Lucis et al 1972;Tanaka et al 1972), sheep (Houpert et al 1997), cattle (Smith et al 1991), and humans (Biego et al 1998). The range of cadmium concentrations in milk was thus reportedly high, ranging from 1 to 30 ppb (Grawe and Oskarsson 2000) with many of the values being much higher (up to 15 times higher) than the Drinking Water Guideline Values (DWGVs).…”
Section: Airmentioning
confidence: 86%
“…Casey and Neville [19] reported Mo levels less than 2 μg/L in HM of US mothers more than 1 month after delivery. Biego et al [20] reported Mo contents of 4±3 μg/L in mature HM from French mothers. As dietary intake influences Mo concentration in HM, in those populations with higher Mo intake, such as the Japanese, higher Mo contents will be found in the HM of local women [21].…”
Section: Mo Concentration In Hm and Infant Formulasmentioning
confidence: 98%